2008
DOI: 10.1007/s11186-007-9052-y
|View full text |Cite
|
Sign up to set email alerts
|

Bourdieu and organizational analysis

Abstract: Despite some promising steps in the right direction, organizational analysis has yet to exploit fully the theoretical and empirical possibilities inherent in the writings of Pierre Bourdieu. While certain concepts associated with his thought, such as field and capital, are already widely known in the organizational literature, the specific ways in which these terms are being used provide ample evidence that the full significance of his relational mode of thought has yet to be sufficiently apprehended. Moreover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
491
0
36

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 643 publications
(553 citation statements)
references
References 102 publications
3
491
0
36
Order By: Relevance
“…In contrast with other theories, such as the Bourdieusian sociology (Emirbayer & Johnson, 2008), the EW framework does not claim to be a complete sociological theory which explains all aspects of social life. On the contrary, it has maintained constant dialogue with other approaches such as the economies of conventions (for a review see Biggart & Beamish (2003) or Actor Network Theory (Guggenheim & Potthast, 2012).…”
Section: Concluding Thoughts: Where To From Here?mentioning
confidence: 86%
See 1 more Smart Citation
“…In contrast with other theories, such as the Bourdieusian sociology (Emirbayer & Johnson, 2008), the EW framework does not claim to be a complete sociological theory which explains all aspects of social life. On the contrary, it has maintained constant dialogue with other approaches such as the economies of conventions (for a review see Biggart & Beamish (2003) or Actor Network Theory (Guggenheim & Potthast, 2012).…”
Section: Concluding Thoughts: Where To From Here?mentioning
confidence: 86%
“…In these authors' view, and using their terminology, social actors with critical competencies will voice their concerns about the situation (critique), suggest and advocate for alternate, presumably more "acceptable" courses of action (justification) and assess action outcomes (both real and imagined) against the criteria they deemed were most appropriate (evaluation (Golsorkhi, Leca, Lounsbury, & Ramirez, 2009), explain practice (Golsorkhi, 2016;Gomez, 2015), and have even suggested a Bourdieu-based approach for studying organizations (Emirbayer & Johnson, 2008), others have suggested that the EW framework is a better lens for arriving at a fuller understanding of organizational practices more generally (Denis et al, 2007).…”
Section: Intellectual Origins Of the Economies Of Worthmentioning
confidence: 99%
“…Seguindo sua analogia com um jogo, Bourdieu e Wacquant (2012) comparam os diferentes tipos de capital como cartas de um baralho, sendo que o valor relativo de cada uma delas muda de acordo com o jogo em questão. Os capitais servem, portanto, como armas na luta por ascendência em um campo (Emirbayer & Johnson, 2008).…”
Section: Os Campos De Poder E a Dinâmica De Capitaisunclassified
“…Entretanto, campos específicos podem se organizar por meio de outros princípios de diferenciação, propiciando o surgimento de outros tipos de capitais mais restritos a estruturação desses campos (EMIRBAYER; JOHNSON, 2008). Então, além destes capitais citados, existem outros mais, na quantidade em que forem identificados e constituírem valor de distinção em campos específicos.…”
Section: Mozar José De Brito and Alessandra Souza Perez Riveraunclassified